2023
DOI: 10.3390/cosmetics10060157
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacy and Fragrances: Traditional and Current Use of Plants and Their Extracts

Francisco José González-Minero,
Luis Bravo-Díaz,
Esteban Moreno-Toral

Abstract: This paper aims to establish a current relationship between pharmaceutical sciences andthe development of perfumes and fragrances, which bring significant economic benefits. For this purpose, historical data are used as a starting point, and galenic, chemical and botanical aspects are discussed in a transversal way. Sources such as Web of Science (WOS) and databases such as Scopus, monographs and various web pages (where scientific–technical documents appear) were used. The results and discussion are based on … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…For example, Rosamah et al [1] investigated the pharmacological significance of Macaranga in dermatological diseases; Udegbunam et al [18] confirmed the therapeutic activity of Crinum jagus in wound healing; and Anacardium occidentale extracts were tested on pathogenic microbes to verify its usefulness in skin care cosmetics by Gonçalves and Gobbo [19]. There are also many similar studies, but this information is scattered in the literature, which may account for the fact that none of the many cosmetic plants recognized by the European Pharmacopoeia are of West African origin [20]. This also underscores the significance of studies in this field.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Rosamah et al [1] investigated the pharmacological significance of Macaranga in dermatological diseases; Udegbunam et al [18] confirmed the therapeutic activity of Crinum jagus in wound healing; and Anacardium occidentale extracts were tested on pathogenic microbes to verify its usefulness in skin care cosmetics by Gonçalves and Gobbo [19]. There are also many similar studies, but this information is scattered in the literature, which may account for the fact that none of the many cosmetic plants recognized by the European Pharmacopoeia are of West African origin [20]. This also underscores the significance of studies in this field.…”
Section: Introductionmentioning
confidence: 99%